1990
DOI: 10.1080/01431169008955179
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of lithological units in airborne SAR images using new texture features

Abstract: Synthetic Aperture Radar (SAR) images are used increasingly in applications of remotely-sensed data for land-use investigation and in the recognition of geological features. This is because SAR images are rich in textural information and textural characteristics of an image are found to be useful in identification of lithological units. For this reason, the automatic processing and interpretation of SAR images are often focused on texture analysis, including the extraction of textural information, textural fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…For example, He and Wang [37] demonstrated that, for airborne SAR -band data on lithological units, features derived from texture spectrum fared better than the co-occurrence method [68]. An in-depth comparative study of five texture algorithms [2] reported that no universally best feature set, among the five different texture algorithms chosen, was found when the data from six frequency bands (of a TM image of a mountainous region) were used.…”
Section: B Texture Algorithmsmentioning
confidence: 99%
“…For example, He and Wang [37] demonstrated that, for airborne SAR -band data on lithological units, features derived from texture spectrum fared better than the co-occurrence method [68]. An in-depth comparative study of five texture algorithms [2] reported that no universally best feature set, among the five different texture algorithms chosen, was found when the data from six frequency bands (of a TM image of a mountainous region) were used.…”
Section: B Texture Algorithmsmentioning
confidence: 99%
“…Various ground condition factors, such as roughness, soil moisture, and slope, have an influence on the backscatter coefficients (Engman and Wang 1987, He and Wang 1990, Bayer et al 1991, Evans et al 1992. Therefore, if pyroclastic flows or lahars changed the land surfaces so that their SAR backscatter coefficients increased or decreased considerably, then the difference (subtraction of intensity values) between a pair of SAR backscatter coefficient images taken before and after the event might 1932…”
Section: Backscatter Approachmentioning
confidence: 98%
“…Meanwhile, textural information and textural characteristics obtained from SAR images have also been proved to be useful in the recognition of lithological units [27,34]. The backscatter coefficients VV and VH were chosen for grey level co-occurrence matrix (GLCM) [45] analysis.…”
Section: Sentinel-1 Preprocessingmentioning
confidence: 99%